Persuasive Strategies in WHO Media Briefings on the Bundibugyo Ebola Outbreak - Khrisna Adji Maulidi; Zaki Zaki; Alfina Alfia Zahra; Farida Nurul Rahmawati (Yayasan Citra Dharma Cindekia, 2026)
The 2026 outbreak of the Bundibugyo strain of Ebola virus disease in the Democratic Republic of the Congo (DRC) and Uganda posed significant challenges to global health governance due to the limited availability of effective biomedical interventions. In such circumstances, communication became a strategic instrument for maintaining public trust and managing societal responses to the crisis. This study aims to analyze the rhetorical strategies employed by the World Health Organization (WHO) in its official media briefing on the Ebola Bundibugyo outbreak through the perspective of Aristotelian rhetoric. Using a qualitative descriptive approach and rhetorical criticism method, this research examines the transcript of WHO’s media briefing delivered on May 20, 2026. The data were analyzed based on Aristotle’s three rhetorical appeals: ethos, pathos, and logos. The findings reveal that WHO constructed ethos through international legal legitimacy and global institutional collaboration, utilized pathos to manage public anxiety and foster international solidarity, and employed logos by presenting epidemiological evidence and fact-based arguments to justify its response to the outbreak. The study demonstrates that rhetoric plays a crucial role in maintaining institutional legitimacy and strengthening public trust during global health emergencies. Furthermore, the findings confirm the continued relevance of Aristotelian rhetoric in understanding contemporary health crisis communication practices.